Rancangan Aplikasi Inventarisir Bahan Pembuat Mukena pada PT. Tatuis Bogor dengan Menggunakan Java - Ega Shela Marsiani (Universitas Indraprasta PGRI Jakarta, 2018)
The purpose of the research is to provide the warehouse staff with convenience to process inventory data so that they can give fast, precise and accurate information. The research method used for the design of this application system is a Grounded Research method. After designing the system of inventory data input application, the researcher then draws a conclusion that the application using Netbeans and IReport softwares can generate more interactive appearance and provide convenience for the PT. Tatuis warehouse staff. Further, PT. Tatuis offers excellent service and produces the goods of high quality. Therefore, to make it more effective and efficient, PT. Tatuis needs a good and user-friendly data storage system to draw up the inventory of mukena fabric